2012
DOI: 10.3238/arztebl.2012.0857
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Hallux Valgus

Abstract: The clinical outcome of present treatments seems to be good in most cases, but large-scale randomized trials are still needed to verify the efficacy of the wide variety of operations and fixation techniques that are currently being offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
2
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 42 publications
3
72
2
12
Order By: Relevance
“…Despite a higher satisfaction rate of 93% among patients in this study, compared with the 85% satisfaction rate for hallux valgus surgery reported in the recent literature, 24 31% of them still have some degree of residual pain at 6 months after surgery, whereas 9% of them were not totally pain free at the 2-year follow-up. Chou et al followed 98 patients who underwent foot and ankle surgery and concluded that preoperative pain intensity was a significant predictor for pain score at 3 days after surgery, whereas age and gender were not.…”
Section: Discussioncontrasting
confidence: 77%
“…Despite a higher satisfaction rate of 93% among patients in this study, compared with the 85% satisfaction rate for hallux valgus surgery reported in the recent literature, 24 31% of them still have some degree of residual pain at 6 months after surgery, whereas 9% of them were not totally pain free at the 2-year follow-up. Chou et al followed 98 patients who underwent foot and ankle surgery and concluded that preoperative pain intensity was a significant predictor for pain score at 3 days after surgery, whereas age and gender were not.…”
Section: Discussioncontrasting
confidence: 77%
“…Currently, therapies vary by the severity of the deformity, ranging from non-operative medications and inlays under the forefoot to surgical procedures such as osteotomies or arthrodesis. Within all of these procedures, however, challenges remain, clinical indications vary and high-level evidence is scarce regarding when to use specific operative techniques over others [3]. …”
Section: Future Implicationsmentioning
confidence: 99%
“…A small number of methods include osteotomies in the shaft. Bone correction in the proximal aspect and arthrodesis of the TMT-I joint are reserved for larger IM angles and severe to extreme hallux valgus deformities [8] The goal of any corrective osteotomy in combination with a soft tissue release is the reduction of a pathological Ist intermetatarsal angle and the correction of the hallux valgus angle. However, a number of additional parameters must be taken into account.…”
Section: Introductionmentioning
confidence: 99%